Impacts of Spirituality on Health Status of HIV/AIDS Infected People: A Study of HIV/AIDS Control Centers in District Gujrat and Sargodha, Punjab, Pakistan (Journal of Social Sciences Review, 2023)
Spirituality is a complex and multilayered construct that can incorporate the internal, external, personal, emotional and physical expression of the sacred expression. Spirituality refers to different prospects for different people, such as believing in a higher power, inner peace, finding a higher purpose in life, and connectedness with self, others and the natural world, among others. Spirituality has a significant association with the life of human beings and is a greater source of positive deeds, which has a great concern in an individual's personal, social, physical and economic situation. Throughout the world, especially in developing countries like Pakistan, individuals living with HIV face several stressors regarding the chronicity of their diseases and experience a very high level of post-traumatic stress. In this study, researchers examined the impacts of spirituality on the health condition of HIV patients by applying quantitative research methods & techniques. Data were collected from patients registered at HIV/AIDS control centres of districts Gujrat and Sargodha. Non-random convenience sampling techniques were applied, and primary data was collected through a structured questionnaire. Advanced statistical software SPSS-21 was used for empirical and reliable results. The findings of the study indicated that spirituality has significantly positive impacts on the psycho-social and physical health conditions of HIV patients.
Keywords: Spirituality; Religious Practices; HIV Infection; Coping Strategies; Social Stigma; HIV/AIDS